Respuesta :

1luke

Answer:

x^2+x-4

Step-by-step explanation:

(f-g)=(x^2+1)-(5-x)

     =x^2+1-5+x

     =x^2+x-4

The result for the given function is  (f – g)(x) = [tex]x^{2}[/tex] + [tex]x[/tex] - 4.

Function

What is a function?

A function is an association between inputs in which every input is connected to only one output.

Subtraction property of functions:

If two functions are such that f(x) and g(x), have limits at the same values (say a), the limit of (f - g)(x) is the difference between the two limits at an as 'x' tends to 'a', according to the subtraction property for limits.

(f - g)(x) = f(x) - g (x)

Calculation for the value of given function.

Function f(x) is given as [tex]x^{2}[/tex] + 1.

Function g(x) is given as 5 - [tex]x[/tex].

By the subtraction formula of functions,

(f - g)(x) = [tex]x^{2}[/tex] + 1 - (5 - [tex]x[/tex])

            = [tex]x^{2}[/tex] + 1 - 5 + [tex]x[/tex]

           = [tex]x^{2}[/tex] + [tex]x[/tex] - 4

Therefore, the value of the function comes out to be

(f - g)(x) =  x² + x - 4

To know more about addition and subtraction of functions; here

https://brainly.com/question/14630324

#SPJ2